Pendampingan Menyusun Laporan Keuangan Sederhana Sesuai Standar Akuntansi di Apotek Bima Farma - Arnova, Iwin; Yulianasari, Nina; Agrisshandra, Dera Arya; Febriani, Zhendrina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service activity aims to provide understanding and training for the managers of Bima Farma Pharmacy on Jl. Depati Payung Negara, RT.3/RW.3, Betungan, Selebar District, Bengkulu City in making financial reports. This community service activity was carried out on October 9, 2024 at 14.00 WIB. This activity was attended by the owners and employees of Bima Farma Pharmacy. The activity was carried out in the form of counseling and training in preparing financial reports. The results of community service activities can increase knowledge and skills in business management through simple and easy-to-implement bookkeeping/accounting.